PENDAPATAN DAN PENGELUARAN RUMAHTANGGA PETANI JAMBU BIJI (Psidium guajava L.) DI DESA PERAWANG BARAT KECAMATAN TUALANG KABUPATEN SIAK - Subakri Sudradjat; Sisca Vaulina (UIR Press, 2023)
Guava farming is a relatively easy activity that doesn't require extensive land. Farmers can achieve significant profits because guava prices tend to be high. This research aims to analyze: (1) the characteristics of guava farmers; (2) the income structure of guava farmers' households; (3) the expenditure of guava farmers' households; and (4) the dominant factors influencing the expenditure of guava farmers. This research was conducted using a survey method and was conducted in Perawang Barat Village, Tualang Sub-district, Siak Regency. The respondents consist of all guava farmers, totaling 31 individuals. Data analysis involves qualitative and quantitative descriptive analysis. The research results showed the characteristics of guava farmers, with an average farmer age of 42.70 years, an average education level of 9.53 years, an average farming experience of 7.57 years, and an average family size of 4 members. The largest household income came from guava farming income, reaching 81.00%. Guava farmers' household expenditures were primarily allocated to non-food expenses, averaging IDR 2,686,819.18 per month, or IDR 32,241,830.11 per year (63.90%). The most dominant factors influencing guava farmers' household expenditure were income and the number of family members, explaining approximately 79.30% of the variation in expenditure.